Architectural and planning features of the village of Hengdaohezi - Tceluiko, Dmitry; Bazilevich, Evgeny (project baikal, 2026)
This article analyzes the planning structure and architectural heritage of Hengdaohezi, one of the most completely preserved station complexes of the Chinese Eastern Railway. It examines the settlement’s development in challenging terrain, its functional zoning, and the spatial logic of its development. Particular attention is paid to the completed and planned departmental buildings of the CER, their architectural solutions, and their role in shaping the village’s appearance. Hengdaohezi is considered a unique example of the adaptation of Russian architectural and engineering traditions to the Manchurian context.